An ultralight and thin metasurface for radar-infrared bi-stealth applications. (10th October 2017) - Zhang, C; Yang, J; Yuan, W; Zhao, J; Dai, J Y; Guo, T C; Liang, J; Xu, G Y; Cheng, Q; Cui, T J
Abstract: We present a thin metasurface with large microwave absorptivity and low infrared emissivity simultaneously. By properly tuning the resonance peaks and impedance of the meta-atom, broadband microwave absorptivity greater than 90% from 8.2 to 16.0 GHz is achieved. In the meantime, owing to large coverage of periodic metal patches on the top surface, low infrared emissivity is exhibited in the infrared region (IR) of 8 µ m–14 µ m. The excellent agreement between numerical simulation and experimental result demonstrates the good performance of the proposed metasurface. Due to the usage of polymethacrylimide (PMI) and polyethylene terephthalate (PET) as the substrate, the metasurface is especially advantageous for the light weight, making it a favorite in real engineering applications.